STRATEGI PEMBELAJARAN GURU PENDIDIKAN AGAMA HINDU SEBAGAI UPAYA PEMBENTUKAN PERILAKU GURUBHAKTI PESERTA DIDIK DI KELAS XI IPA DAN IPS SEKOLAH MENENGAH ATAS SARASWATI 1 DENPASAR - Yanti, Ni Made Satya Novita; nanduq, ferdinandus; Sukma Muniksu, I Made (UPADHYAYA: JURNAL PENELITIAN PENDIDIKAN, 2023)
Learning strategies in learning Hindu Religious Education and Budi Pekerti are very important to be able to minimize the deviant behavior of students. So that with the learning strategy children's behavior can be formed through the teachings of Hinduism. Applying religious teachings to everyday life will foster good behavior. The problems that will be discussed include (1) How is the reality of the application of Hindu religious education teacher learning strategies as an effort to shape students' gurubhakti behavior in class XI IPA and IPS Saraswati 1 Denpasar Senior High School, (2) How is the weakness of Hindu religious education teacher learning strategies as an effort to shape students' gurubhakti behavior in class XI IPA and IPS Saraswati 1 Denpasar Senior High School, (3) How is the effort to optimize Hindu religious education teacher learning strategies in shaping students' gurubhakti behavior in class XI IPA and IPS Saraswati 1 Denpasar Senior High School. Religious Education Teachers as an effort to shape gurubhakti behavior using the development of Hindu religious teachings using the Discovery Learning strategy. This strategy makes students active in seeking knowledge. Teachers in improving students' Gurubhakti behavior relate learning material to everyday life. Weaknesses and efforts to optimize Hindu Religious Education teacher learning strategies as an effort to shape students' gurubhakti behavior can be divided into several factors, namely: learning method selection strategies, learning material development selection strategies, learning media selection strategies, classroom management development strategies, and evaluation selection strategies. Keywords: Learning Strategy, Hinduism, Gurubhakti Behavior, Students, SMA Saraswati 1 Denpasar